DAMPAK MEDIA SOSIAL TIKTOK TERHADAP AKHLAK REMAJA DI DESA LUHU, KECAMATAN HUAMUAL, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Hasbi Assiddiky Suneth; Andi Hasriani; Martini; Nur Setiawati; Ratika Nengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of TikTok by adolescents in Luhu Village, Huamual District, West Seram Regency, Maluku Province, and its impact on adolescent morality. The method used was a qualitative approach with data collection through observation, in-depth interviews with 25 informants, and documentation. Data analysis was carried out through data reduction, presentation, and drawing conclusions. The results showed that adolescents use TikTok intensively, averaging 3–4 hours per day, primarily for watching entertainment content, dancing, and viral trends. Positive impacts found include increased creativity, ease of access to information, and the ability to express themselves. Meanwhile, negative impacts include decreased direct social interaction, imitation of content or language that does not conform to social and religious norms, and impaired learning discipline. Environmental factors, such as minimal parental supervision, exacerbate these negative influences. This study emphasizes the need for parents, educators, and the community to provide guidance and supervision so that TikTok use can be directed towards positive things.